The impact of social media influencers on the purchasing intention of the young Chinese consumer - Lu, Shen (2024)
The power of social media influencers is growing along with live shopping and social media marketing. Recently, it has also been clear how influential and valuable Chinese influencers are economically. By making use of the source trust model and the associated theories of the emotion and connection between consumers and influencers, this study investigates the effect of social media influencers on the consumption intentions of young Chinese consumers. The trustworthiness, expertise attractiveness of social media influencers , affection and connection between consumers and influencers have a beneficial impact on the consumption intention of young Chinese consumers, according to a questionnaire survey of 253 young consumers in China. And these elements are crucial, and they have a good relationship with one another.